The truth about negotiating with someone you hate ... or love - Thompson, Leigh L. (Truth about (FT Press), 2011)
"This Element is an excerpt from The Truth About Negotiations (9780136007364) by Leigh Thompson. How to negotiate successfully with people you can't stand--and people you can't resist."--Resource description page.